2023
DOI: 10.51327/agbc9783
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Turnover Intention: The Mediating Role of Work Engagement

Abstract: Guided by job demands-resources (JD-R) theory, this paper aims to explore the relationship between religiosity and turnover intention through the mediating role of work engagement. Using a survey questionnaire, data were collected from 338 employees working in the telecom sector in Jordan. Partial least squares structural equation modelling (PLS-SEM) was used to test the hypotheses. The findings show that religiosity is positively related to work engagement, while work engagement is negatively related to turno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Broadly speaking, previous studies have confirmed the mediating role of work engagement among several antecedents and outcomes (Abualigah & Koburtay, 2022; Jyoti, 2021; Karatepe & Demir, 2014; Memon et al, 2020; Mostafa, 2019). For example, Memon et al (2020) found that the relationship between HRM practices and turnover intention is mediated by work engagement.…”
Section: Literature Review and Hypothesismentioning
confidence: 75%
“…Broadly speaking, previous studies have confirmed the mediating role of work engagement among several antecedents and outcomes (Abualigah & Koburtay, 2022; Jyoti, 2021; Karatepe & Demir, 2014; Memon et al, 2020; Mostafa, 2019). For example, Memon et al (2020) found that the relationship between HRM practices and turnover intention is mediated by work engagement.…”
Section: Literature Review and Hypothesismentioning
confidence: 75%
“…Nevertheless, prior work on the relationship between supervisor support and work engagement has been somewhat difficult to comprehend across different sectors and occupations (Hidayah Ibrahim et al , 2019), and yet, the role of personal resources in enhancing work engagement and job-related outcomes is largely neglected (Abualigah et al , 2021; Agarwal and Gupta, 2018). Furthermore, existing literature has overlooked the potential impact of employee religiosity although the latter is an important personal resource for enhancing work engagement and employee commitment (Abualigah and Koburtay, 2022; Abu Bakar et al , 2018; Baker and Lee, 2020) particularly in unique institutional contexts like the one under investigation in the current study, where religious values and beliefs significantly influence and shape people management practices (Abualigah et al , 2022; Haak-Saheem and Darwish, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of personal resources in predicting job-related outcomes, little theorising of the job demands-resources (JD-R) theory has been conducted to explore the interaction effect between job and personal resources in facilitating work engagement (Grover et al , 2018). For example, Abualigah and Koburtay (2022) recently found that work engagement mediated the relationship between religiosity and turnover intention. However, they have called for more research to further investigate the role of religiosity in the workplace.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations